2014
DOI: 10.15540/nr.1.3-4.219
|View full text |Cite
|
Sign up to set email alerts
|

Treating Trauma Survivors with Neurofeedback: A Grounded Theory Study

Abstract: Neuroscience, the mental health field, and the concept of trauma as an underlying factor in mental and physical disorders have been inextricably linked since the inception of the mental health professions. Numerous quantitative studies have indicated that neurofeedback may be effective in ameliorating trauma symptoms; however, there is a paucity of research exploring the factors that produce those positive outcomes. The purpose of this qualitative grounded theory study was to explore the factors and processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…2 ) The results in this study demonstrated that the move of location to a bigger and brighter room promoted the feasibility as it generated a nicer atmosphere, perceived to have a calming impact. This is in line with previous research by Currie et al, exploring in uencing factors on treatment outcomes when treating trauma survivors with NF (32). Like statements from our participants, Currie and colleagues described how the therapeutic process begins the moment the patient enters the door.…”
Section: Discussion Of Themessupporting
confidence: 89%
“…2 ) The results in this study demonstrated that the move of location to a bigger and brighter room promoted the feasibility as it generated a nicer atmosphere, perceived to have a calming impact. This is in line with previous research by Currie et al, exploring in uencing factors on treatment outcomes when treating trauma survivors with NF (32). Like statements from our participants, Currie and colleagues described how the therapeutic process begins the moment the patient enters the door.…”
Section: Discussion Of Themessupporting
confidence: 89%
“…These results are similar to those described by participants in a grounded theory study who described taking the “leap” into neurofeedback because results were so compelling they couldn’t walk away. [22] Participants in both studies recognized neurofeedback doesn’t fix the brain but prompts learning of self-regulation, and the brain healing itself. This ability is due to the principle of neuroplasticity, which is the ability of the nervous system to respond to stimuli (such as neurofeedback) and reorganize its structure, function, and connections.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Research suggests nutrition, allergies, toxins, and infections could affect neurofeedback outcomes, as well as client factors such as motivation, culture, and family system. [22] Our participants reported aging, diet, inflammation, and medication use may slow or reduce an individual's response to neurofeedback. Research is needed to confirm these observations, which are particularly relevant to cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely to remember to apply techniques after an incident (%) Trauma exposure coding was undertaken using basic thematic analysis (Currie et al, 2014;Skinner et al, 2019) to see whether it was possible to detect any typical 'first trauma exposures' 7 in new recruits. Themes were extracted from monthly check-ins from March onwards 8 (n ¼ 71) and the difficult or traumatic incidents participants selected in session 2 training (n ¼ 32) and session 3 control group training (n ¼ 28).…”
mentioning
confidence: 99%